Seks Bebas dalam Perspektif Hadis - Mutiara Mutiara; Muhammad Alif (Program Studi Ilmu Hadis STAIN Mandailing Natal, 2024)
Free sex or in Islam it is called Zina is a social phenomenon that refers to sexual behavior in which individuals engage in sex without long-term commitments, such as marriage or exclusive monogamous relationships. This phenomenon has become a controversial topic in modern culture and has given rise to different views, approaches and impacts depending on the societal perspective. This study uses a qualitative approach with thematic methods. The urgency of this research is the rampant cases of free sex in Indonesia where the majority of the population is Muslim. The formal object of this study is the understanding and view of Islam on free sex which is formulated based on the hadith themes. The results of this study aim to find out how Islam views free sex behavior. The discussion of this study explains that free sex is strictly prohibited in Islam, free sex is one of the signs of the coming of the apocalypse, and punishment for those who commit adultery. Overall, the hadith perspective teaches that free sex or adultery is an act that is condemned and not permissible in Islam. These hadiths emphasize the importance of maintaining honor, marrying as a legal means of having sexual relations, and stipulating harsh punishments for those involved in such acts. Islam encourages individuals to live a legal and responsible sexual life in a legal marriage. The conclusion of this study is that the act of free sex has many negative impacts on the perpetrator, it is easy to contract a disease and free sex is one of the prohibited acts and is a big sin.